A Comparatives Study of How Social Media Influences The Buying Motivation of Gen Y and Gen Z - Novita, Dian; Lina, Lia Febria (JURNAL BISNIS STRATEGI, 2024)
This study primarily conducted an in-depth investigation to obtain information about factors that make the young generation purchase smartphones influenced by social media. The analysis focused on the millennial or the 'Me' generation (Gen Y) and the 'True' generation (Gen Z). These two generations represent the present-day dominant youth cohort. This qualitative study utilized the technique of conducting semi-structured interviews for data collection. No differences were found in Gen Z's and Y's smartphone purchasing motivations. The buying decisions of both generations were equally and materially influenced by genuine reviews on social media, especially content in the form of social media live streams such as YouTube and TikTok videos, especially when well-known influencers conveyed pertinent information. The interviews revealed the distinctive features of the two generations studied: they are rational in making purchase decisions and consider both quality and price. Unlike Gen Y, Gen Z   does not like to compare new products against other or previous products because it takes advantage of its proximity to the manufacturing company to obtain adequate information about a product. Practically, it can be a reference for smartphone retailers to better understand youth purchase behavior.